2018
DOI: 10.1371/journal.pone.0207600
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study for three-dimensional assessment of laminar pore structure in patients with glaucoma, as measured with swept source optical coherence tomography

Abstract: PurposeTo develop a method to quantify, based on swept-source optical coherence tomography (OCT), the 3D structure of the laminar pores in patients with glaucoma.MethodsThis retrospective study examined 160 laminar pores from 8 eyes of 8 cases: 4 normal subjects and 4 open-angle glaucoma (OAG) patients. We reconstructed 3D volume data for a 3 x 3 mm disc, using a method similar to OCT angiography, and segmented the structure of the lamina cribrosa. Then, we manually segmented each laminar pore in sequential C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A retrospective study showed that differences in LC pore shape and size of glaucomatous eyes have also been associated with damage to ON [ 12 ] using optic disc photographs. Based on images obtained by swept-source optical coherence tomography (OCT), Omodaka et al found that glaucoma patients had a smaller area and 3D volume of LC pores, probably due to the expanding area of connective tissue [ 13 ]. Elongation of lamina pores was more evident in primary open-angle glaucoma eyes than in normal eyes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study showed that differences in LC pore shape and size of glaucomatous eyes have also been associated with damage to ON [ 12 ] using optic disc photographs. Based on images obtained by swept-source optical coherence tomography (OCT), Omodaka et al found that glaucoma patients had a smaller area and 3D volume of LC pores, probably due to the expanding area of connective tissue [ 13 ]. Elongation of lamina pores was more evident in primary open-angle glaucoma eyes than in normal eyes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%